Epithelial thymoma in a feline – Case report (Research, Society and Development, 2021)
The aim of the present study was to report a case of epithelial thymoma in a feline, referred for diagnosis at the Regional Diagnostic Laboratory, Faculty of Veterinary Medicine, Federal University of Pelotas (LRD/FV/UFPel). According to the responsible clinical veterinarian, the animal presented a history of vomiting and hyporexia, rapidly progressing to death, and the cadaver was sent to the LRD/FV/UFPel. At necropsy, a light brown mass was observed, lobulated and apparently encapsulated in the anterior mediastinum. Fragments of the mediastinal mass and organs of the abdominal and thoracic cavities, as well as the brain were collected and fixed in 10% buffered formalin. After 48 hours the tissue samples were cleaved, routinely processed and stained using the hematoxylin and eosin technique. Selected sections of the mediastinal mass were collected on a positive slide to perform the immunohistochemical technique (IHC). The antibodies used in IHC were anti-cytokeratin, CD3 and CD79a. In the histopathological evaluation of the mediastinal mass, proliferation of thymic epithelial cells was observed among non-neoplastic lymphocytes. In the IHC technique, neoplastic cells were positive for cytokeratin. The diagnosis of epithelial thymoma in this case was based on macroscopic and microscopic findings and confirmed by immunohistochemistry.